Everything Old Is New Again: The Evolution of Generic Appraisal at Library and Archives Canada - Giesbrecht, Rebecca; Murdock Smith, Jenna (Archivaria, 2017)
The concept of “generic appraisal” was part of the original conceptualization of macroappraisal as it was developed at the thenNational Archives of Canada (now Library and Archives Canada) in 1990. This hypothesis, that cross-institutional functional patterns and areas where institutions shared common characteristics could support its implementation, was never fully put into practice. In response to a new focus on recordkeeping in 2009, archivists developed tools based on common activities performed by many or all government institutions. This enabled a re-examination of generic appraisal in more depth. Over the next five years, generic appraisal grew to inform and fully support the new approach to government records disposition at Library and Archives Canada (LAC). This article provides an account of the evolution of generic appraisal at LAC, and of how it facilitated the redesign of a disposition program that puts macroappraisal theory into practice in a more effective, efficient, and accountable manner. RÉSUMÉ Le concept de « l’évaluation générique » faisait partie de la conceptualisation d’origine de la macro-évaluation telle qu’elle a été développée aux anciennes Archives nationales du Canada (maintenant Bibliothèque et Archives Canada) en 1990. Cette hypothèse – que des courants fonctionnels pan-institutionnels et des domaines où des institutions partagent des caractéristiques communes peuvent appuyer sa réalisation – n’a jamais été entièrement mise en pratique. Lorsque l’accent a été placé sur la tenue de documents, en 2009, les archivistes ont développé des outils basés sur les activités communes réalisées par la plupart ou par toutes les institutions gouvernementales. Ceci a permis un réexamen plus approfondi de l’évaluation générique. Au courant des cinq années suivantes, l’évaluation générique s’est étendue pour influencer et appuyer pleinement la nouvelle approche de disposition des documents gouvernementaux à Bibliothèque et Archives Canada (BAC). Cet article fournit un compte rendu de l’évolution de l’évaluation générique à BAC, et de la façon dont elle a facilité la reconceptualisation du programme de disposition qui met la théorie de la macro-évaluation en pratique d’une manière plus efficace, efficiente et responsable.